Building your influence: the role of the smart sustainability leader [version 1; peer review: 2 approved] - Janet Haddock-Fraser; David Gorman (Emerald Publishing, 2020)
Anyone seeking to influence another is a potential leader.  Within higher education, determining what an institution should undertake on sustainability can be daunting.  Sustainability leaders face labyrinthine, multifaceted sub-cultures, influencers and viewpoints across staff, students, government, business and alumni all with an opinion on whether, how and in what order of priority sustainability should be taken forward.  In this paper we take on this challenge by synthesising and critically evaluating core principles and working models for influencing and leading for sustainability in higher education. We identify a series of eight challenges affecting delivery of sustainability and seek to understand how conceptual models and principles in sustainability decision-making and leadership could address these. We draw on the experience of both authors, in tandem with comments from workshop and leadership training programme participants who attended the Environmental Association for Universities and Colleges (EAUC) Leadership Lab training in the UK, as well as reflections arising in a detailed case study from the University of Edinburgh.  We bring key insights from theory and practice for the benefits of individuals or teams seeking to influence and persuade key decision-makers to embrace the sustainability agenda.